2015
DOI: 10.1002/pat.3454
|View full text |Cite
|
Sign up to set email alerts
|

Influence of multiwall carbon nanotube (MWCNT) dispersion on ignition of poly(dimethylsiloxane)–MWCNT composites

Abstract: Poly(dimethylsiloxane) (PDMS) filled with low contents of multiwall carbon nanotubes (MWCNT) was prepared using different ways to monitor the dispersion of MWCNT. The influence of the dispersion on thermal conductivity and transmittance was measured. High degree of transparence can be achieved with 0.02 phr of well dispersed MWCNT. Time-to-ignition (TTI) was also measured on 2-or 4-mm-thick specimens heated using radiative unidirectional source. Time-to-ignition was found to decrease with the incorporation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…It is noted that the same content of PPMS‐CNT shows lower T on than that of PPMS in the EP matrix. This result can be ascribed to the presence of CNTs will improve the thermal conductivity of the composites concomitant with the increase of heat transfer, as reported by Sonnier, which gives an explanation of the decreased TTI of the composites in cone calorimeter test. In addition, the PMLR values of the samples from EP‐1 to EP‐4 are 13.3%, 23.7%, 32.4%, and 27.2% lower respectively than the value of EP‐0.…”
Section: Resultssupporting
confidence: 73%
“…It is noted that the same content of PPMS‐CNT shows lower T on than that of PPMS in the EP matrix. This result can be ascribed to the presence of CNTs will improve the thermal conductivity of the composites concomitant with the increase of heat transfer, as reported by Sonnier, which gives an explanation of the decreased TTI of the composites in cone calorimeter test. In addition, the PMLR values of the samples from EP‐1 to EP‐4 are 13.3%, 23.7%, 32.4%, and 27.2% lower respectively than the value of EP‐0.…”
Section: Resultssupporting
confidence: 73%
“…The thin films containing aluminum particles were also characterized by an “epiradiator test” instrumented with an infrared pyrometer (Optris, Berlin, Germany) as already described (see Figure 1 in [ 11 ]). Pure LDPE film was not tested using this device.…”
Section: Methodsmentioning
confidence: 99%
“…In polypropylene filled with various carbon nanoparticles, Dittrich et al have shown that the heat absorption coefficient increases with nanoparticles leading to lower TTI, even if this effect is partly counterbalanced by the increase in thermal conductivity [ 9 , 10 ]. The dispersion of fillers, particularly nanoparticles, also significantly affects the absorption in-depth [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion of particles could affect the TTI through several phenomena. Particles decrease the heat absorption in-depth (Fina et al, 2013;Sonnier et al, 2015) or can modify the emissivity or the thermal conductivity (Kashiwagi et al, 2004). The decrease of TTI could be due to a modification of heat transfer caused by the presence of aggregates (Clerc et al, 2005;Wang and Zhang, 2012), which increased locally the polymer temperature and the concentration of combustible volatiles in the gaseous phase surrounding the sample (Drysdale, 2011).…”
Section: Flame Retardancymentioning
confidence: 96%